2004
DOI: 10.1097/01.asn.0000129115.69395.65
|View full text |Cite
|
Sign up to set email alerts
|

The Transient Receptor Potential Superfamily of Ion Channels

Abstract: Abstract. The transient receptor potential (TRP) superfamily of proteins is cation-selective ion channels with six predicted transmembrane segments and intracellularly localized amino and carboxyl termini. Members of the TRP superfamily are identified on the basis of amino acid sequence and structural similarity and are classified into TRPC, TRPV, TRPM, TRPP, TRPN, and TRPML subfamilies. TRP channels are widespread and have diverse functions, ranging from thermal, tactile, taste, osmolar, and fluid flow sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 98 publications
(119 reference statements)
0
52
0
Order By: Relevance
“…It does not form functional homodimers, rather heterodimers with TRPC3, -C4, -C5, and/or -C7 (23,24). Furthermore, TRPC1 can associate with polycystic kidney disease 2 (23,25,26) and is embedded in a protein complex that may include caveolin, which contributes to plasma localization of TRPC1 (27). Gene expression of all TRPC1 interaction partners was unchanged in kidneys of ZDF rats, except for reduced expression of TRPC3 (online appendix Table 9).…”
Section: Discussionmentioning
confidence: 99%
“…It does not form functional homodimers, rather heterodimers with TRPC3, -C4, -C5, and/or -C7 (23,24). Furthermore, TRPC1 can associate with polycystic kidney disease 2 (23,25,26) and is embedded in a protein complex that may include caveolin, which contributes to plasma localization of TRPC1 (27). Gene expression of all TRPC1 interaction partners was unchanged in kidneys of ZDF rats, except for reduced expression of TRPC3 (online appendix Table 9).…”
Section: Discussionmentioning
confidence: 99%
“…Thermo-TRP channels, which include TRPV1 (4, 5), TRPV2 (6), TRPV3 (7), TRPV4 (8), TRPM8 (9, 10), and TRPA1 (11), are activated over distinct temperature ranges (1). Combined, these thermo-TRPs account for the detection of the entire spectrum of temperature sensations perceived by mammals.TRP channels consist of six putative transmembrane (TM)-spanning segments flanked by intracellular N-and C-terminal domains (12, 13) of variable length and an ion-conducting poreloop region located between TM segments five and six (12)(13)(14). Residues within the N-and C-terminal regions are proposed to associate with cellular proteins and cytoplasmic factors (15, 16) that determine channel activation properties and subcellular localization.…”
mentioning
confidence: 99%
“…Recent studies have shown that pH regulates the activity of the transient receptor potential vanilloid receptor 6 (TRPV6) epithelial calcium channel (73,74). This channel, present on the brush border membrane (BBM) of the duodenum, is involved in calcium absorption (73).…”
Section: Metabolic Alkalosismentioning
confidence: 99%